Livelihood security through natural resource management in Tehri Himalayas - Kashyap, Poonam; Prusty, A K; Singh, M P; Panwar, A S; Singh, V K (Indian Horticulture, 2019)
The farming system approach is most powerful tool for improving livelihood of small and marginal farmers. It has the main objective of holistic improvement of livelihood, profit maximization and on-farm employment generation through integrated farming system (IFS) approach. The IFS approach along with improved technological interventions may bring long-term farming system sustainability, improve livelihood and generate sufficient local employment which will restrict rural youth migration in hill areas of Uttarakhand. The synergism between different farm enterprises can increase the productivity, profitability and happiness of the farmers.